The psychological outcome and ethical and assistance implications for heart transplant subjects - Puca, Antonio (Medicina e Morale, 1992)
Delirium, psychosis, anxiety, depression, emotional instability, social maladjustment and difficulty in sexual integration are some of the most frequently found phenomena of the various stages of heart transplants. Drawing on the vast amount of literature available the author has highlighted the possible factors and psychological alterations caused by the transplant and/or by the stages of the protocol. He has described the reaction to the drugs, the change of the body image, and has carried out a criticai revision of the psychological and psychiatric reactions to transplants and/or to concomitant factors. Finally the author offers some ethical and assistance suggestions which derive from the description of the possible personality modifications in the subjects who undergo heart transplants.